2012
DOI: 10.31357/fesympo.v15i0.175
|View full text |Cite
|
Sign up to set email alerts
|

STUDY THE EFFECT OF SALINITY AND NUTRIENTS FOR THE GROWTH OF Najas marina AND ITS IMPACT TO AQUATIC BIODIVERSITY IN MADU GANGA RAMSAR WETLAND IN SRI LANKA

Abstract: Madu Ganga is the latest addition to the Ramsar International Convention of Wetlands. Najas marina is an alien aquatic plant and 0.5 m long that are often branched toward the upward portion of the plant. The objective of the study was to study the impact of salinity and nutrients for the growth of Najas marina. Samples were collected for analysed water quality parameters from March, 2006 to January 2007 in the lagoon. Mapping was done using Garmin GPS map 76CS and Arc GIS used to developed maps.Mean nutrient s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
1
3
1
Order By: Relevance
“…Similar observations have been made by Amarathunga et al (2010) in studies carried out in 2006-2007 in this wetland. However, present study indicates that the mean values of most of the physicochemical parameters, namely surface water temperature, TDS, Salinity, pH, BOD5, TDP and TP were not significantly different among the 10 sites studied (p>0.05).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Similar observations have been made by Amarathunga et al (2010) in studies carried out in 2006-2007 in this wetland. However, present study indicates that the mean values of most of the physicochemical parameters, namely surface water temperature, TDS, Salinity, pH, BOD5, TDP and TP were not significantly different among the 10 sites studied (p>0.05).…”
Section: Discussionsupporting
confidence: 76%
“…During the present study, higher values than this were reported in 3 sites namely sites 1, 3 and 6. From March to June, the mean nitrate-N content was higher than that reported by Amarathunga et al (2010). During the present study, high mean salinity of 17.5-19.6 g L in July.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…Being located in the wet zone, draining a small watershed and connecting to the sea through a narrow winding channel 4.6 km long, Madu Ganga also showed a marked zonation in salinity (Table 4). At the marine entrance area salinity ranged from 4.2 to 28 ppt while it was 4-10 ppt for the center of the lagoon and 0-4 ppt towards the freshwater inflow area (Amarathunga et al 2010). Madu Ganga also depicts a typical salinity gradient for a small, seasonally tidal lagoon with a distinct zonation.…”
Section: Koggala Lagoonmentioning
confidence: 95%